Answer:
4.24
Step-by-step explanation:
looked it up on google
google is never wrong
Answer:
(x) =
x + 8
Step-by-step explanation:
let y = f(x) and rearrange making x the subject, that is
y = 9(x - 8) ← divide both sides by 9
= x - 8 ( add 8 to both sides )
+ 8 = x
Change y back into terms of x with x =
(x) , thus
(x) =
x + 8
Answer: exact form: y= -23/4
Step-by-step explanation: move all the terms that doesn’t contain “y” to the right side and solve.
Answer:
19.5
Step-by-step explanation:
60 - 40.5 = 19.5.
The answer is 27a^6
Hope this helps.